2009
DOI: 10.1007/s00261-009-9591-y
|View full text |Cite
|
Sign up to set email alerts
|

MDCT with multiplanar reconstruction in the preoperative local staging of rectal tumor

Abstract: MDCT with multiplanar reconstruction is an accurate technique in the preoperative local staging of rectal tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 27 publications
0
29
0
5
Order By: Relevance
“…Ju et al (36) concluded that EUS is superior to spiral CT for the judgment of tumor infiltrate depth and concluded that neither modality provides a satisfactory assessment of lymph node metastasis for rectal cancer. However, Ahmetoğlu et al (37) showed that multidetector CT can be highly accurate in the prediction of T staging, N staging, International Union Against Cancer (IUCC) staging, and mesorectal fascia involvement in the preoperative local staging of rectal cancer. In contrast to these results, Juchems et al (38) stated that multidetector CT fails to reliably identify IUCC I in rectal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ju et al (36) concluded that EUS is superior to spiral CT for the judgment of tumor infiltrate depth and concluded that neither modality provides a satisfactory assessment of lymph node metastasis for rectal cancer. However, Ahmetoğlu et al (37) showed that multidetector CT can be highly accurate in the prediction of T staging, N staging, International Union Against Cancer (IUCC) staging, and mesorectal fascia involvement in the preoperative local staging of rectal cancer. In contrast to these results, Juchems et al (38) stated that multidetector CT fails to reliably identify IUCC I in rectal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Für Fragestellungen, die eine Darstellung der mesorektalen Faszie und die Beziehung des Tumors zu ihr erfordern, weist das MRT aktuell die höchste Sensitivität auf [694]. Das Spiral-CT stellt eine mögliche Alternative dar [688], in der Endosonografie lässt sich die Faszie nicht darstellen.…”
Section: Level Of Evidence 2bunclassified
“…ERUS and PET-CT are not accurate in predicting an involvement of the MRF [3,19]. MDCT might represent an alternative method [20], although it has a low diagnostic value in low-seated tumors and especially in those located in the low anterior rectal wall [3]. …”
Section: Stagingmentioning
confidence: 99%